Analysis Of Factors That Affect Employee Performance - Rahmad Bahagia; Rini Astuti (Journal of International Conference Proceedings (JICP), 2019)
This study aims to determine what factors affect the performance of employees (private companies in the city of Medan). The population in this study were all employees in the city of Medan. The research method used is descriptive quantitative using factor analysis techniques. Where the results of the study stated that there are four dominant factors that influence employee performance decisions, namely employee development, compensation, motivation, and work environment.